Հղիության ելքերը COVID-19 վարակակիրների շրջանում - Աբրահամյան, Ռ․ Ա․; Ղարդյան, Գ. Կ.; Աբրահամյան, Լ. Ռ.; Ավագյան, Տ. Գ.; Շարբատյան, Ա. Ա.; Աբրահամյան, Ս. Հ.; Գրիգորյան, Վ. Ֆ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Учитывая тот факт, что среди беременных, инфицированных COVID-19, существует высокий риск осложнений, было проведено ретроспективное описательное исследование, цель которого – изучить влияние этого вируса на течение и исход беременности. В Республиканском институте репродуктивного здоровья, перинатологии, акушерства, гинекологии проведено описательное исследование путем изучения историй болезни беременных, зараженных COVID-19, находящихся на стационарном лечении с 2020-2022 гг. По результатам исследования было выявлено увеличение частоты преждевременных родов, достоверное увеличение мертворождения, увеличение гипертензивных нарушений беременности, однако, частота осложнений беременности гестозом не изменилась. Частота передачи инфекции от зараженных COVID-19 беременных новорожденным соответствует данным международных исследований. Taking into account the fact that there is a high risk of complications among pregnant women infected with COVID-19, a retrospective descriptive study was performed, the purpose of which was to investigate the effect of this infection on the course and outcome of pregnancy. An observational study was conducted by studying the medical records of pregnant women infected with COVID-19 who received inpatient treatment from 2020 to 2022 in Republican Institute of Reproductive health, perinatology, obstetrics and gynecology. According to the results of the research, there was an increase in the frequency of premature birth, a significant increase in the rate of stillbirth, an increase in the frequency of hypertensive disorders of pregnancy, but the frequency of complications of pregnancies with preeclampsia did not change. The frequency of transmission of infection from COVID-19 positive pregnant women to newborns is in line with the data of international studies.
Keywords: Հղիություն